Lessons Learnt from Post-Infectious IBS - Sarna, Sushil (Frontiers in Physiology, 2011)
The development of IBS symptoms– altered bowel function and abdominal cramping in a subset of adult subjects exposed to severe enteric infections opened up an unprecedented opportunity to understand the etiology of this poorly understood disorder. Perhaps, for the reasons that these symptoms follow a severe enteric infection, and mucosal biopsy tissues are readily available, the focus of most studies thus far has been to show that mild/low-grade mucosal inflammation persisting after the initial infection has subsided causes the IBS symptoms. Parallel studies in non-infectious IBS patients, who did not have prior enteritis, showed similar mild mucosal inflammation. Together, these studies examined the mucosal infiltration of specific immune cells, increase of select inflammatory mediators, mast cell and enterochromafin cell hyperplasia and epithelial permeability. In spite of the fact that the data on these topics were not consistent among different studies and clinical trials with prednisone, fluoxetine and kitotifen failed to provide relief of IBS symptoms, the predominant conclusions were that mild mucosal inflammation is the cause of IBS symptoms. However, the circular smooth muscle cells, and myenteric neurons are the primary regulators of gut motility function, while primary afferent neurons and CNS play essential roles in induction of visceral hypersensitivity - no explanation was provided as to how mild mucosal inflammation causes dysfunction in cells far removed. Accumulating evidence shows that mild mucosal inflammation in IBS patients is in physiological range. It has little deleterious effects on cells within its own environment and therefore it is unlikely to affect cells in the muscularis externa. This review discusses the disconnect between the focus on mild/low-grade mucosal inflammation and the potential mechanisms and molecular dysfunctions in smooth muscle cells, myenteric neurons and primary afferent neurons that may underlie IBS symptoms.